Subacromial Impingement Syndrome Caused by a Voluminous Subdeltoid Lipoma - Jean-Christophe Murray; Stéphane Pelet (Case Reports in Orthopedics)
Subacromial impingement syndrome is a clinical diagnosis encompassing a spectrum of possible etiologies, including subacromial bursitis, rotator cuff tendinopathy, and partial- to full-thickness rotator cuff tears. This report presents an unusual case of subdeltoid lipoma causing extrinsic compression and subacromial impingement syndrome. The patient, a 60-year-old man, presented to our institution with a few years' history of nontraumatic, posteriorly localized throbbing pain in his right shoulder. Despite a well-followed 6-months physiotherapy program, the patient was still suffering from his right shoulder. The MRI scan revealed a well-circumscribed 6 cm × 2 cm × 5 cm homogenous lesion compatible with a subdeltoid intermuscular lipoma. The mass was excised en bloc, and subsequent histopathologic examination confirmed a benign lipoma. At 6-months follow-up, the patient was asymptomatic with a complete return to his activities. Based on this case and a review of the literature, a subacromial lipoma has to be included in the differential diagnosis of a subacromial impingement syndrome refractory to nonoperative treatment. Complementary imaging modalities are required only after a failed conservative management to assess the exact etiology and successfully direct the surgical treatment.